The Basic Concepts, Applications, and Research Trends in Pragmatics - Sookde, Chaded (Journal of Social Sciences and Humanities Research in Asia, 2025)
The purpose of this research was to: 1) examine the situation of sexual abuse through cyberspace among lower secondary school students; 2) explore life skills concepts for preventing the risks of sexual abuse through cyberspace; and 3) develop a life skills program to enhance the competencies of lower secondary school students in preventing such risks. This study used an action research design. The research process consisted of five steps: 1) analysing the situation of sexual abuse through cyberspace among lower secondary school students; 2) reviewing the literature on life skills concepts for preventing such risks, based on secondary data; 3) designing and developing programs consistent with life skills concepts to strengthen students’ competencies in prevention; 4) creating tools and a life skills program to prevent sexual abuse through cyberspace; and 5) evaluating the quality of the program by assessing its relevance and appropriateness with three experts. The findings showed that most victims of sexual abuse through cyberspace were aged 8-14, followed by those aged 15-17, under 8, and 18 years, respectively. Key concepts for prevention included competencies, life skills, sexual education, cyberspace, adolescent development, and learning theories. The life skills program developed for early adolescents took the form of structured activities designed to strengthen their ability to cope effectively with risks in the cyber world.